Mannose-Binding Lectin 2 Gene Polymorphism during Pandemic: COVID-19 Family - Tufan Tukek; Sacide Pehlivan; Yasemin Oyaci; Ummuhan Isoglu-Alkac (Global Medical Genetics, 2022)
Mannose-binding lectin 2 (MBL2) is a serine protease which is believed to be an important factor in the inherited immune system. In this article, we present a coronavirus disease 2019 (COVID-19) family of five patients: a 56-year-old father, a 51-year-old mother, two sons aged 23 and 21 years, and a 15-year-old daughter. According to the results of MBL2 rs1800450 variant analysis performed, the father had homozygous mutant, the mother had homozygous normal, and the three children had heterozygous mutant genotype. When we compared the clinical parameters and genotypes, MBL2 gene polymorphism plays a very important role in COVID-19 susceptibility and severe disease. The family, which makes up our study, is the proof of this situation, and it contains important implications for host factors and COVID-19.